EFFICACY OF A FIXED COMBINATION OF LOSARTAN AND AMLODIPINE IN PATIENTS WITH ARTERIAL HYPERTENSION: SEASONAL FEATURES - M. D. Smirnova; T. V. Fofanova; Z. N. Blankova; M. V. Vitsenya; T. V. Tsybulskaya; Yu. F. Dianova; F. T. Ageev (Евразийский Кардиологический Журнал)
The goal is to evaluate the efficacy and security of treatment of patients with arterial hypertension (AH) during the heat wave of a fixed combination of ARBS+ACC (losartan+amlodipine).Materials and methods. Included 26 patients with hypertension 1 and 2 degrees from 42 to 81 years. All patients underwent measurement of office blood pressure, 24h ambulatory BP monitoring, Self-measurement of BP (Home BP ), electrocardiography, biochemical analysis of blood, estimation of osmolarity of blood, questionnaire: visual analogue scale, a questionnaire for patients exposed to heat, the test of adherence to treatment Moriscos-Green. Estimated diaries of self-control of blood pressure. The inclusion visit took place in spring 2016, 1st visit was in May-June 2016, 2nd - during heat waves, 3rd -September-October 2016.Results. The observed decrease in systolic blood pressure and diastolic blood pressure (p=0.000) to the target values, preserved for the whole period of observation. According to the diaries of selfcontrol of blood pressure controlled blood pressure 81% of patients. During a heat wave, this value decreased to 58%, in autumn - to 63%. The 3rd visit achieved a reduction in heart rate at -6.0 (-11.1; and 2.8) beats/min; p=0.007; the decline in uric acid level c of 415.3 to 346.2 mmol/l (p=0.04) and creatinine on the 2nd visit compared to baseline (p=0.02). According to 24h ambulatory BP monitoring, 24h ambulatory BP monitoring, during a single visit, the mean SBP decreased from 139 to 121 mm Hg. (P=0.04) and DBP from 88 to 76 mm Hg. (P=0.04) in the daytime and the tendency to decrease SBP variability from 12 to 10 mm (p=0.07). At the end of the study, the indicators remained stable. The mean value of SBP decreased at night to the third visit from 116 to 110.5 mm Hg. (P=0.04). During the heat wave, a larger mean SBP and DBP was recorded compared with the third visit (p=0.04). A correlation was found between the mean DBP value (r=0.725, p=0.03), the SBP time index (r=0.695, p=0.04) and the SBP time (r=0.787, p=0.02) at night and Quality of life Electrolyte shifts and increasing the osmolarity of the blood during heat waves have not been identified. There is a growing commitment therapy (p=0.04) and quality of life to 20.0 (7.4; 23.3); p=0.000 by visual analogue scale.Conclusion. Fixed combination of losartan and amlodipine (Lorenza) is an effective, safe and may be recommended for hypertensive patients during heat wave and seasonal cold snap.